Penerapan Modul Praktikum Berbasis Masalah Untuk Meningkatkan Pemahaman Konsep dan Keterampilan Proses Sains Siswa - Ulhusna, Syifa; Firmansyah, Juli; Azzarkasyi, Muhammad; Rizal, Syamsul (Journal of Technology and Literacy in Education, 2024)
This research aims to measure the percentage of students' achievement of Understanding Concepts and Science Process Skills in learning through the application of the Problem-Based Practicum Module on the concept of light refraction. The method used is Quasi-experimental with a one group pretest and posttest design. The subjects of this research were 27 students of SMP Negeri 1 Indrapuri in the odd semester of 2023. The test instrument used for the concept understanding test was in the form of a multilevel description consisting of the ability to explain the concept of a given case (P), the ability to determine the laws of physics that explain the case (Q), the ability to provide additional case examples regarding related law (R) and define that law (S). The research results showed that students achieved an understanding of the concept of light refraction at the complete understanding (MSU) level after following the practicum using a problem-based module. Therefore, it can be concluded that the level of understanding of the concept of the practical practicum module has increased effectively, reaching 33% in the posttest from 0% understanding completely through the problem-based practicum module in the pretest. Meanwhile, the results of research on science process skills show that there are 7 items of Science Process Skills that were revealed from the results of data collection, namely the items observation, classification, making conclusions, predicting, communicating, making hypotheses, and experimenting. Based on the research results, it can be concluded that the level of science process skills in the high category is found in the observation indicator at 74.07%, the indicator for making conclusions at 85.19%, the indicator for predicting at 77.78%, and the indicator for experimenting at 81.48%, while in the low category, the communication indicator is 44.44% and the hypothesis making indicator is 38.27%.